Research trends on land use changes during 1991–2015: A Bibliometric Analysis - J. Zhang; B. Wang; X. Chen; X. Wu; D. Zhang (International Association of Lowland Technology, 2019)
Land use changes, as a practical and advanced space exploration technology, offered a lot of valuable data about the earth surface for global analysis, detailed assessment, environmental monitoring, mapping, change detection, disaster management, and civil and military intelligence. To provide a better understanding of global trends in land use changes research over the past 25 years and offer an informed perspective on future research, a bibliometric analysis of published land use changes research was conducted to evaluate current research trends from various perspectives quantitatively and qualitatively for the period of 1991-2015 based on SCIE&SSCI databases. This study is concentrated on the analysis of scientific outputs, research directions, source journals, author performance and their contribution, the distribution of research countries/territories as well as institutions and their collaboration and temporal trends in keywords usage.